Dreams of falling - White, Karen (Karen S.) (Berkley, 2018)
"From the New York Times bestselling author of The Night the Lights Went Out comes an exquisite new novel about best friends, family ties and the love that can both strengthen and break those bonds. New York Times bestselling author Karen White crafts evocative relationships in this new contemporary women's fiction novel about best friends who share a devastating secret, set in the Lowcountry of South Carolina. It's been nine years since Larkin fled Georgetown, South Carolina, vowing never to go back. But when she finds out that her mother has disappeared, she knows she has no choice but to return to the place that she both loves and dreads--and to the family and friends who never stopped wishing for her to come home. Ivy, Larkin's mother, is discovered in the burned out wreckage of her family's ancestral rice plantation, badly injured and unconscious. No one knows why Ivy was there, but as Larkin digs for answers, she uncovers secrets kept for nearly 50 years. Secrets that lead back to the past, to the friendship between three girls on the brink of womanhood who swore that they would be friends forever, but who found that vow tested in heartbreaking ways"--